French Unionism Militant - Skelton, O. D. (Journal of Political Economy, 1909)
"So another tradition vanishes," exclaimed a witty Frenchwoman a few years ago o,n returning from a magnificent state festival given by M. le ministre Millerand, one-time socialist comrade. "Under the Restoration a Liberal was defined as an escaped coinvict. Thirty years ago it was agreed that every Republican wore dirty linen and was careless of his finger-nails,. Later the Socialist took the place of the Republican. Next ?"' The next has come. The syndicalist, exponent of the new revolutionary unionism, has displaced the socialist as chief bogey of the bourgeois world. And not oif the bourgeois world alone, for the new movement is causing almost as much uneasiness to the parliamientary socialist as to the philistine. France presents today the piquant spectacle of the accredited defenders of the Marxist faith acting as a moderating force, and for their pains being labeled as reactionary.2